Advances in Internet, Data and Web Technologies The 8th International Conference on Emerging Internet, Data and Web Technologies (EIDWT-2020) - Barolli, Leonard; Okada, Yoshihiro; Amato, Flora (Lecture Notes on Data Engineering and Communications Technologies, 2020)
XXVI, 576 p. 345 illus., 235 illus. in color.